2016
DOI: 10.1007/s11427-016-0025-0
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Kindlin-2 induces cardiac dysfunction in mice

Abstract: Kindlin-2, a member of the Kindlin family focal adhesion proteins, plays an important role in cardiac development. It is known that defects in the Z-disc proteins lead to hypertrophic cardiomyopathy (HCM) or dilated cardiomyopathy (DCM). Our previous investigation showed that Kindlin-2 is mainly localized at the Z-disc and depletion of Kindlin-2 disrupts the structure of the Z-Disc. Here, we reported that depletion of Kindlin-2 leads to the disordered myocardial fibers, fractured and vacuolar degeneration in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Several independent teams have reported paradoxical results about the role of Kindlin-2 in fibrotic diseases. Wei et al demonstrated that blockade of Kindlin-2 in vivo ameliorated unilateral ureteral obstruction (UUO)-induced renal fibrosis 21 ; on the contrary, postnatal loss of Kindlin-2 led to the enlargement of the heart and extensive fibrosis 22 , 23 . In this study, we clearly revealed that Kindlin-2 +/− mice were protected against CCl 4 -induced liver fibrosis, which is in line with our data of in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several independent teams have reported paradoxical results about the role of Kindlin-2 in fibrotic diseases. Wei et al demonstrated that blockade of Kindlin-2 in vivo ameliorated unilateral ureteral obstruction (UUO)-induced renal fibrosis 21 ; on the contrary, postnatal loss of Kindlin-2 led to the enlargement of the heart and extensive fibrosis 22 , 23 . In this study, we clearly revealed that Kindlin-2 +/− mice were protected against CCl 4 -induced liver fibrosis, which is in line with our data of in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kindlin-2 was also reported to play an essential role in fibrotic disorders. Wei and co-workers demonstrated that Kindlin-2 is highly expressed in human and mouse fibrotic kidney, and depletion of Kindlin-2 attenuates experimental renal fibrosis 21 ; on the contrary, knockout of Kindlin-2 expression in cardiac myocyte or depletion of Kindlin-2 resulted in progressive cardiac fibrosis 22 , 23 . Currently, the effect of Kindlin-2 in liver fibrosis remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Kindlin‐2 has been shown to promote tumour invasion and metastasis 54,55 . It is also essential for preserving integrity of the heart, vascular permeability in angiogenesis, chondrogenesis, regulation of podocyte structure and function, control of adipogenesis and lipid metabolism as well as bone homeostasis 56‐61 . Kindlins protect cells against oxidative damage 62‐65 .…”
Section: Discussionmentioning
confidence: 99%
“…Kindlin-2 collaborates with α-actinin-2 and β1 integrin to preserve the structural integrity of the Z-disc in cardiac muscle tissue (33). The elimination of Kindlin-2 in murine models results in the disruption of the Z-disc structure, subsequently causing cardiac malfunction (34,35). Increasingly, research studies are documenting the existence of multiple potentially causative mutations in patients diagnosed with Dilated Cardiomyopathy (DCM).…”
Section: Etiologymentioning
confidence: 99%